PENGGUNAAN SET MODEL DAN PERMAINAN REMI BILBUL DALAM PEMBELAJARAN PENJUMLAHAN BILANGAN BULAT DI KELAS IV SD - Umi Puji Lestari; Ratu Ilma Indra Putri; Yusuf Hartono (Universitas Negeri Malang, 2015)
Abstract: The current study was intended to investigate the teaching and learning situations on addition of integer teaching and learning at the fourth grade of elementary schools which used the set model and the integer play card. The method utilized was design research. The Realistic Mathematics Education (RME) was the basis for the context design and activities. The results of the study suggested that the activities of making notes on the money transactions in the form of two-color coins and playing integer cards could trigger the students’ thinking strategy in adding the integer. Abstrak: penelitian ini bertujuan untuk menginvestigasi situasi pembelajaran penjumlahan bilangan bulat di kelas IV SD dengan menggunakan set model dan permainan remi bilbul. Metode yang digunakan adalah design research. PMRI mendasari desain konteks dan aktivitas. Hasil penelitian menunjukkan aktivitas mencatat transaksi keuangan dalam keping dua warna dan permainan remi bilbul dapat memunculkan strategi berpikir siswa dalam menjumlahkan bilangan bulat.